Latina/o/x Studies and Biblical Studies - Hidalgo, Jacqueline M. (2020)
This essay introduces Latina/o/x studies for a biblical studies audience. It examines crucial themes that bridge Latina/o/x studies and biblical studies, themes such as identity and difference with special attention to ethnicity and race; also migration with attention to homing, diaspora, transnationalism, and citizenship. The place of Latina/o/x studies in relevant Hebrew Bible and New Testament scholarship on these topics is also discussed. Ultimately this essay argues that Latina/o/x studies’ epistemological commitments to complexity, relationality, particularity, and collaborative knowledge-making can help ground critical interpretive approaches in biblical studies. This essay also imagines a way that biblical studies—capaciously encompassing the study of Jewish and Christian literature in the ancient world as well as Jewish and Christian biblical reception and rejection histories, and the very category of scriptures more broadly—could deepen Latina/o/x studies own thinking about canon formation and history.